Mesobathic chondrichthyes of the Juan Fernández seamounts: are they different from those of the central Chilean continental slope? - Isabel Andrade; Germán Pequeño (Revista de Biología Tropical, 2008)
We compared the geographic distribution of groups of chondrychthid fishes of two physically proximal, although geographically different, regions that include the Juan Fernández seamounts and the central Chilean continental slope, both sampled at mesopelagic and mesobenthonic depths. The ridge is in the Nazca Plate, while the slope region in on the South American Plate, and is closer to the South American continent. We found six species of Chondrichthyes for the seamounts (four orders, four families). The slope sampling produced ten species of Chondrichthyes, of which Torpedo tremens De Buen 1959, was the only species in common with the Juan Fernández area. There are clear differences between the Chondrichthyes of the two regions. These fisheries require adequate administrative modes. Rev. Biol. Trop. 56 (1): 181-190. Epub 2008 March 31. Se realizó un estudio de distribución geográfica comparativa entre conjuntos de peces condrictios de dos sectores geográficamente cercanos, pero geológicamente distintos, el sector este de la cordillera sumergida de Juan Fernández y el talud continental de Chile central, a profundidades mesopelágicas y mesobentónicas. La cordillera está sobre la placa de Nazca, el talud en la Sudamericana. Comparamos familias, géneros y especies, mediante el índice de Jaccard. Hay seis especies de condrictios en los montes submarinos (cuatro órdenes y cuatro familias). El talud tiene diez especies, y únicamente comparte con la cordillera a Torpedo tremens De Buen 1959. Estos condrictios requieren modos administrativo-pesqueros adecuados.